Profile of Implementation Direct Instruction and Physics Problem Solving Skills of Senior High School Students - M Raynaldi Rosyidi Zamil; Eko Hariyono; Binar Kurnia Prahani (Jurnal Ilmiah Pendidikan Fisika, 2021)
This research aims to determine the profile of high school student's ability to solve physics problems by applying the direct instruction learning model based on audiovisual Sparkol video scribe media. The research used is preliminary. This study uses the method of applying the ACCES problem-solving skill level criteria (A-Assen the problem, C-Create a drawing, C-Conceptualize the strategy, E-Execute the solution, S-Scritinize your Desult), with 101 students of class XI SMA Negeri 1 Now. Data were obtained by using problem-solving tests, questionnaires, and interviews with students and teachers of physics subjects. Data analysis was carried out in a qualitative descriptive manner. The results of the study: (1) Based on the results of the problem-solving tests that students have in the low category with a score range of 0 to 10, 87 students, 12 students in the medium category with a score range of 11 to 20, and 2 students in the high category with a score range of 21. up to 30. (2) Based on the results of the questionnaire on student learning experiences and teacher performance in delivering physics learning in class, it can be seen that: (a) students do not like physics subjects, (b) teachers often teach using the lecture method, rarely use other learning media, (c) students have difficulty working on the problem-solving skills test. (3) results Based on teacher and student interviews, it can be seen that problem-solving in physics is important to know. According to students, the obstacles in improving problem-solving skills were due to a lack of interest in physics subjects, and the characteristics of physics subjects were quite complicated. Likewise, the teacher's response cannot be made well because of student interest, so that improving problem-solving skills cannot be done effectively and can only be done in certain classes. Thus, it can be said that the problem-solving skill profile based on the ACCES criteria in class XI students of SMA Negeri 1 Sekaran can be categorized as low and difficult to train.